The impact of Agriculture Land Development Programme (ALDP) of Orang Asli resettlement plan scheme (RPS) in Pahang, Malaysia - Man, Norsida; Hamid, Halilah; Abu Samah, Asnarulkhadi (Universiti Putra Malaysia Press, 2013)
In the 1960s, Malaysia like other newly independent nations used modernisation of agriculture systems as a priority for its rural development plan. Orang Asli, as one of the target groups were e xposed to commercial and cash crops to replace their traditional ways of farming. The government believed the best way to improve the economic conditions of rural people was to introduce the oil palm, rubber, temperate crops and other commercial plants. The Agriculture Land Development Programme(ALDP) is one of the programmes under the Economic Development Programme implemented by Department of Orang Asli Development (JAKOA) to address the high incidence of poverty among Orang Asli population. The objectives of this study are (1) to identify the level of impact of ALDP and (2) to determine the relationship between selected demographic factor and the impact of ALDP. This study only focuses on Orang Asli who were involved in ALDP oil palm plantation scheme in all RPS in Pahang. This is a descriptive study using the quantitative method of a questionnaire as a tool to collect data from the respondents. This study involved 170 respondents who received monthly dividends between RM400 until RM800. The results of the study revealed that the level of impact is moderate in all aspects discussed. Meanwhile, the Pearson Product-Moment Correlation result showed that income category and land size have significant positive relationship with level of ALDP impact. Some recommendation was made due to results of study for future improvements of ALDP.